The Team-Based Learning (TBL) methodology articulated with the TBL Active platform in Accounting learning in the technical course in Administration - Sandra Cristina Pelegrini Giacomell; Raquel Rosan Christino Gitahy; Adriana Aparecida de Lima Terçariol (Universidad de Costa Rica, 2021)
The current article constitutes in an excerpt from the Mater's Degree research entitled as "The use of the Team-Based Learning (TBL) Methodology allied to technology: Perceptions over the learning of basic accounting in the Technical Course in Administration". The question that guided the development of this Master's research was: can the Team-Based Learning (TBL) active methodology allied to digital technology provide collective learning of basic accounting concepts in the Technical Course in Administration? Based on this inquiry, the main purpose of the study presented in this article was to evaluate the contributions of the use of the TBL methodology, combined with the free platform TBL Active, which was created to assist in the application of this active methodology, in learning the basic concepts of Accounting in the technical course in Administration. The approach adopted was the quali-quantitative one since this study combined qualitative and quantitative methods in an intervention research. The development of this research took place in a public school, in the technical course in Administration, placed in the countryside of São Paulo/Brazil. Therefore, the participants were set as a class of 34 students. The observation and application of surveys were used as data collection tools. The main results showed the occurrence of collective learning of Accounting. Other than that, when comparing the individual answers to the collective answers, it showed significative successes. The active participation and the significative learning of the given content were achieved by means of the Team-Based Learning Methodology.